Implementation of the Balanced Scorecard for Performance Evaluation at the West Java Provincial Plantation Service - Rhaka Fathi Ruhiyat; Hafid Aditya Pradesa; Alikha Novira; Reni Wijayanti (Jurnal Manajemen dan Perbankan (JUMPA), 2025)
Performance assessment in public sector organizations has experienced significant strategic changes and dynamics, no longer focusing solely on financial aspects and customer (service user) perspectives. This study aims to evaluate the performance of the Plantation Office of West Java Province through the implementation of the balanced scorecard (BSC). Using a quantitative approach, the study utilizes secondary data such as satisfaction surveys, annual reports, and the 2023 performance accountability report of the Plantation Office of West Java Province, analyzed using a scoring system. The study reveals that overall, the performance of the Plantation Office is rated as very good based on the four perspectives of the BSC. However, certain areas require more attention, particularly in terms of program implementation, workload balance, and employee capacity development. The study recommends that the Plantation Office continues to optimize the implementation of the BSC, enhance service quality to the public, and strengthen more sustainable human resource development. Further research is expected to deepen the application of the BSC in the public sector, enrich performance indicators, and explore the design and implementation of the BSC in various public sector organizations. Abstract​​​​​ - Evaluasi kinerja di sektor organisasi publik telah mengalami perubahan dan dinamika strategis yang signifikan, tidak hanya menekankan pada aspek keuangan dan aspek pelanggan (pengguna) layanan. Penelitian ini bertujuan untuk mengevaluasi kinerja Dinas Perkebunan Provinsi Jawa Barat melalui implementasi balanced scorecard (BSC). Dengan metode kuantitatif, penelitian ini menggunakan data sekunder seperti survei kepuasan, laporan tahunan, dan laporan akuntabilitas kinerja Dinas Perkebunan Provinsi Jawa Barat tahun 2023 yang dianalisis menggunakan sistem penilaian. Penelitian menunjukkan bahwa secara keseluruhan, kinerja Dinas Perkebunan dinilai sangat baik, berdasarkan empat perspektif dalam BSC. Namun, beberapa area masih memerlukan perhatian lebih, terutama dalam hal realisasi program kerja, keseimbangan beban kerja, dan pengembangan kapasitas karyawan. Penelitian ini merekomendasikan agar Dinas Perkebunan terus mengoptimalkan implementasi BSC, meningkatkan kualitas layanan kepada masyarakat, dan memperkuat pengembangan sumber daya manusia yang lebih berkelanjutan. Penelitian ini dapat memperdalam implementasi BSC di sektor publik, memperkaya indikator kinerja, serta mempelajari lebih lanjut desain dan implementasi BSC di berbagai sektor organisasi.